Community Perception on Malaria in Urban Area of Tumkur - Vidya KR; Lohit K; Narasimha BC; Swamy RM (National Journal of Community Medicine, 2021)
Background: Malaria is the parasitic disease that affects people around the world with highest rate of morbidity and mortality. There is a need to intensify efforts at grassroots levels to reach the most vulnerable people with advanced health care and technologies Methodology: A community based cross sectional study was conducted in the urban slum area of Tumkur. All individuals aged more than 20 years of age, permanent residents, who were present on the day of survey were included in the study. Multistage random sampling method used to select participants, semi-structured questionnaire using interview method used to collect data. Results: A total of 112 families were interviewed during the study. Among respondents 56.3% were females. Majority were in the age group of 20-39 years (50%). Regarding housing condition 67.9% of the houses were pukka while 18.3% of the houses. Majority of participants (76.7%) knew about malaria. Among them 60.5% said malaria is a communicable. Conclusion: The study revealed that perception about malaria was satisfactory and there was varied perception about causes, spread of disease, and source of infection and prevention of malaria disease.